Pandangan dan Perjuangan Ideologis Hizbut Tahrir Indonesia (HTI) dalam Sistem Kenegaraan di Indonesia - Arif, Syaiful (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2016)
Hizbut Tahrir Indonesia (HTI) is a trans-national Islamic movement and carrying the re-establishment of a global Islamic caliphate. Theoretically, this establishment addressed for the sake of Islamic law at the level of politics and society. The problem is, when the ideas and struggles were developed in Indonesia, which has the basic form of the state and the final state, namely the Republic of Indonesia (NKRI) and the Pancasila, the struggle HTI is part of the defamation against the state. Although this political struggle will not succeed, but it is quite effective conduct of delegitimation on national awareness among Muslims that they managed to recruit a member. This article will explain the state of political ideology and agenda HTI. Therefore, this paper aims to explore the views HTI about sharia and its position for the state system of caliphate and the glory (political) Islam that sought to establish global world as well as in Indonesia nationally. In addition, HTI put ideological struggle in the context of the ideological threat on Pancasila and the Homeland, because the idea khilafahnya necessarily contradictory with the nation-state of the Republic of Indonesia. The data of this article comes from the literature. The results of the literature review were then analyzed through political discourse and the Islamic state, which raises the style Islamic political discourse in the context of political discourse HTI in Indonesia. The article concludes, HTI do delegitimation nationality, Pancasila and state buildings Homeland. It departs from the perspective of Islamic law formalist and holistic, where Sharia law is understood as the rules governing the whole life of the community, through the formalization into the constitution and state law. Cita re-establishment of the Islamic caliphate is a structural condition for the enforcement of Islamic Shari’a. Hizbut Tahrir Indonesia (HTI) merupakan gerakan Islam transnasional dan mengusung pendirian kembali khilafah Islamiyyah secara global. Secara teoretis, pendirian ini ditujukan demi tegaknya syariat Islam pada level politik dan kemasyarakatan. Persoalannya, ketika gagasan dan perjuangan tersebut dikembangkan di Indonesia, yang memiliki bentuk negara dan dasar negara final, yakni Negara Kesatuan Republik Indonesia (NKRI) dan Pancasila, maka perjuangan HTI merupakan bagian dari upaya penistaan terhadap negara. Meskipun secara politik perjuangan ini tidak akan berhasil, namun cukup efektif melakukan delegitimasi atas wawasan kebangsaan di kalangan Muslim yang berhasil mereka rekrut menjadi anggota. Tulisan ini hendak menjelaskan ideologi politik dan agenda kenegaraan HTI. Karena itu, tulisan ini bertujuan menggali pandangan HTI tentang syariat dan posisinya bagi sistem kenegaraan khilafah dan kejayaan (politik) Islam yang ingin ditegakkan di dunia global serta di Indonesia secara nasional. Di samping itu, menempatkan perjuangan ideologis HTI dalam konteks ancaman ideologis atas Pancasila dan NKRI, karena gagasan khilafahnya tentu kontradiktif dengan negarabangsa Republik Indonesia. Data-data artikel ini berasal dari studi pustaka. Hasil dari studi pustaka itu kemudian ditelaah melalui diskursus politik dan kenegaraan Islam, sehingga memunculkan diskursus politik Islam ala HTI dalam konteks wacana politik di Indonesia. Artikel ini menyimpulkan, HTI melakukan delegitimasi kebangsaan, Pancasila dan bangunan kenegaraan NKRI. Hal ini berangkat dari pandangan tentang syariat Islam yang formalis dan holistik, di mana syariat dipahami sebagai tata aturan hukum seluruh kehidupan masyarakat, melalui formalisasi ke dalam konstitusi dan hukum negara. Cita pendirian kembali khilafah Islamiyyah merupakan kondisi struktural bagi tegaknya syariat Islam ini.